Analysis of the Role of Public Prosecutors in Proving Corruption Crimes in Indonesia - Sri Yulianingsih (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2026)
Corruption is a criminal offense that significantly affects state stability and public trust in Indonesia’s legal system. In the process of proving corruption cases, public prosecutors play an important role in preparing indictments, presenting evidence, and constructing legal arguments in court proceedings. This study aims to analyze the role of public prosecutors in proving corruption crimes, identify obstacles in the evidentiary process, and examine the effectiveness of prosecution strategies used in court. This research employed a qualitative method with an empirical juridical (*socio-legal research*) approach. The research sample consisted of 10 informants, including 5 public prosecutors, 2 corruption court judges, 2 criminal law academics, and 1 advocate. Data were collected through in-depth interviews, literature studies, and documentation studies. The findings indicate that the success of proving corruption cases is strongly influenced by the prosecutors’ ability to connect evidence with the elements of the alleged criminal offense. In addition, electronic evidence and the development of digital-based corruption practices have become new challenges in the evidentiary process. This study is expected to provide theoretical and practical contributions to improving the effectiveness of corruption crime prosecution in Indonesia.